The effects on the acoustic parameters and auditory-perceptive characteristics of voice in children submitted to adenoidectomy with or without tonsillectomy. (October 2019) - Pinto, Isabel; Firmino-Machado, João; Castro, Eugénia; Alves, Sandra; Helena, Diamantino; Condé, Artur
Abstract: Objectives: To analyse the possible changes on the acoustic parameters and auditory-perceptive characteristics of children's voice after adenoidectomy with or without tonsillectomy. Methods: Prospective cohort study of children aged 5–12 years at one month before surgery (t0) and one (t1), three (t3) and six (t6) months after adenoidectomy with or without tonsillectomy. On each assessment the acoustic parameters (fundamental frequency, jitter %, shimmer % and harmonics-to-noise ratio) and auditory-perceptive analysis (nasal resonance, loudness, pitch, GRBAS scale and maximum phonation time) were recorded. Results: A total of 51 children were considered for data analysis . Nasal resonance revealed a significant decrease in the number of cases with hyponasality, from 86.3% at t0 to 12.8% at t1 (p < 0.001), 2.3% at t3 (p < 0.001) and 2.8% at t6 (p < 0.001). This improvement was maintained during the late follow-up time with no significant difference on nasal resonance between t0 and t3 (p = 0.250) and t3 and t6 (p = 0.250). All children with alteration on the GRBAS scale before the procedure showed a normal voice quality after the surgery. Regarding the acoustic parameters none showed a significant change with the surgery. Conclusions: The results suggest that adenoidectomy with or without tonsillectomy is a safe procedure concerning voice alterations and can improve voice quality and nasal resonance in a sustained manner.